Principal component analysis of the associations between kinetic variables in cutting and jumping, and cutting performance outcome - Welch, N.; Richter, C.; Moran, K.; Franklyn-Miller, A. (The Journal of Strength and Conditioning Research, 2021)
The primary aim of this study was to determine which features within the ground reaction force (GRF) trace during cutting are related to performance outcome in different angled cuts. The secondary aim was to understand the relationship between GRF features in a series of maximum strength, explosive strength, and reactive strength tests, and cutting performance outcome. Twenty-five male intercounty Gaelic football players (23.5 ± 4.2 years, 183 ± 6 cm, and 83 ± 6.9 kg) participated in the study. Subjects completed 110 and 45° cutting tasks, single leg squat jumps, drop landings, drop jumps, and isometric midthigh pulls. A principal component (PC) analysis and simulation approach were applied to the data and correlations between PCs and cutting performance outcome measured. Lower vertical to horizontal impulse ratios (r = -0.70 to -0.46) in both cuts and greater forces over the first 50 ms of ground contact (r = -0.44) in the 110° cut correlated with enhanced cutting performance outcomes. Greater reactive strength index and height in the drop jump (r = -0.51 and -0.54) and greater impulses over the first 25 ms of ground contact in the drop landing (r = 0.49 and 0.70) correlated with enhanced cutting performance outcomes. These results highlight the importance of greater horizontal and rapid force production in cutting and greater reactive strength qualities to enhance cutting performance.